The importance of clinical and histopathological correlation in the diagnosis of skin diseases: An eleven years’ experience - Sami Metin, Mahmut; Atasoy, Mustafa (Annals of Medical Research, 2021)
None
Keywords: Clinicopathological Correlation; Dermatopathology; Skin Biopsy.